A new method for the characterization of hydrides hydrogen tanks dedicated to automotive applications. (20th July 2016) - Chabane, D.; Harel, F.; Djerdir, A.; Candusso, D.; ElKedim, O.; Fenineche, N.
Abstract: In recent years, hydrogen has emerged as one of the best candidates in the field of renewable energy. Hydrogen storage in solid form has created new areas of application. Knowing the thermodynamic parameters of intermetallic compounds featuring stable hydrides is of great importance when using these hydrides in energy sources such as fuel cell generators for embedded or stationary applications. In this work, a new experimental method is described for measuring the hydrogen absorption/desorption characteristics of hydrogen storage material. This method is able to determine the Pressure-Composition-Temperature isotherm of a scale 1 hydride tank used in a fuel cell vehicle. This kind of characterization is useful for optimizing energy management between two vehicle powertrain components: the fuel cell stack and the hydride storage unit. Highlights: A hydrogen storage. Present the methods usually used for hydrogen storage. The different methods used for hydride characterization. Presentation of the new process used for characterization the hydride at tank scale. Measuring the thermodynamics parameters of the hydride.